Isolation of active compound as anti acne from ethanol extract Artocarpus camansi leaves - AZALIA IZDHIHAR AZWAR; MUHAMMAD BAHI; ROSNANI NASUTION; NURDIN NURDIN; MARIANNE MARIANNE (Jurnal Natural, 2023)
Acne vulgaris or acne is a chronic inflammatory skin disease in adolescents and adults affecting one self-confidence. The result of the research shows the ethanol extract, subfraction, pure isolate, and gel extract of Artocarpus camansi are active in inhibiting the growth of Propionibacterium acnes. The ethanol extract with the highest inhibition zone was at the concentration of 0.5 and 2% with 9.1±0.62 mm and 8.5±0.7 mm with the activity of 47.07% and 43% respectively (in comparison with the chloramphenicol 30 μg 19.33±0.47mm). The gel extract had the highest activity at 2%, with an inhibition zone of 8±0.50 mm and the activity of 43.97%. Anti-acne activity for all subfractions had an activity of 32.5-33.3% while the pure isolate was at 42.10 - 45.63%. Physical properties of the gel extract were evaluated for four weeks by examining the pH test obtained with a range of 5.8-6.7, viscosity in the range of 18460-19668 cP, spreadability in the range of 5.45-7.20 cm, adhesion observation above 4 seconds, and homogeneity in a concentration of 0.5-7.5%. The pure isolate has a melting point of 147 ℃, presumed to be γ-sitosterol and appropriate with the screening phytochemicals results with the presence of steroid.